1980
DOI: 10.1185/03007998009112030
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of mefenamic acid and dextropropoxyphene plus paracetamol in an accident and emergency department

Abstract: A randomized double-blind trial was carried out in an accident and emergency department to reassess mefenamic acid as a suitable alternative analgesic to the combination of dextropropoxyphene plus paracetamol. Analysis of data from 87 patients showed that mefenamic acid was equally effective in relieving pain and was less likely to produce adverse side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Several small randomized trials have addressed the combined analgesic efficacy of paracetamol and opioids in patients with pain in general, 8 acute low back pain, 9 soft tissue strains and sprains, 10-12 and postarthroscopy analgesia, 13 but few have compared it with nonsteroidal antiinflammatory drugs. Of these studies, only 1 recruited more than 100 participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several small randomized trials have addressed the combined analgesic efficacy of paracetamol and opioids in patients with pain in general, 8 acute low back pain, 9 soft tissue strains and sprains, 10-12 and postarthroscopy analgesia, 13 but few have compared it with nonsteroidal antiinflammatory drugs. Of these studies, only 1 recruited more than 100 participants.…”
Section: Discussionmentioning
confidence: 99%
“…The value of 13 mm was chosen because studies suggest that this is the minimum change in pain score necessary to achieve clinical significance. 6,8 Pain reduction between the 4 groups was assessed by comparing the mean change in pain score in the first 2 hours or the first 3 days from the baseline. Then analysis of covariance models with the baseline values as the covariate were fitted.…”
Section: Primary Data Analysismentioning
confidence: 99%
“…Stableforth (1977) and Sleet & Khan (1980) addressed the concern which had been expressed about the use of dextropropoxyphene in the accident and emergency department. In controlled trials they showed that mefenamic acid was equally effective and had fewer side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…The excluded analgesics were NSAIDs [ketorolac (Wright et al, 1994;Turturro et al, 1995;Neighbor and Puntillo, 1998;Rainer et al, 2000), mefenamic acid (Stableforth, 1977;Sleet and Khan, 1980), diflunisal (Aghababian, 1986) and piroxicam (Morán, 1990)], opioids [nalbuphine (Stene et al, 1988;Chambers and Guly, 1994;Hyland-McGuire and Guly, 1998;Woollard et al, 2002Woollard et al, , 2004, hydrocodone (Marco et al, 2005) and butorphanol (Scott et al, 1994)] and a type of paracetamol [hydrocodoneacetaminophen (Turturro et al, 1998)]. This may have led to the loss of relevant information for emergency care settings in other countries.…”
Section: Limitations In Literature Search and Analysismentioning
confidence: 99%